Analysis of Curriculum Policy on the Performance of Early Childhood Education Teachers - I Made Ardika Yasa; I Wayan Widiana; I Gede Ratnaya (Syntax Corporation Indonesia, 2023)
This research aims to analyze the impact of curriculum policies on teacher performance in the context of early childhood education. The research method used in this study is policy analysis. Data was collected through literature study, interviews with education stakeholders, and direct observation of teacher performance. The collected data was then analyzed qualitatively to identify the impact of curriculum policies on teacher performance. The research results show that curriculum policies have a significant influence on the performance of early childhood education teachers. Implementing a clear and comprehensive curriculum helps teachers develop learning plans that suit children's needs. Apart from that, a curriculum that is closely linked to teacher competency standards also encourages improvements in teachers' skills and knowledge in teaching. However, this research also identified several challenges faced by teachers in dealing with curriculum policies. This research concludes that curriculum policy plays an important role in improving the performance of early childhood education teachers. To maximize the positive impact, greater efforts need to be made to increase the support and resources available to teachers, as well as improve their training and understanding regarding the implementation of the new curriculum. Thus, it can be hoped that the quality of early childhood education will continue to improve.